Analisis Hidrodinamika dan Karakteristik Pressure Drop pada Fotobioreaktor Flat-Panel Sistem Closed-Loop Menggunakan Computational Fluid Dynamics - hidayat, alif nur; Sena , Boni; Siswadi; Agustin , Aisyah; Aprellya, Putri; Herlambang, Pratikara (Universitas Muhammadiyah Metro, 2026)
Hydrodynamic performance plays a crucial role in determining flow distribution and hydraulic losses inside flat-panel photobioreaktor systems. This study aims to investigate the flow characteristics and pressure drop behavior of a closed-loop flat-panel photobioreaktor using a Computational Fluid Dynamics (CFD) approach. A three-dimensional steady and incompressible laminar model was employed with water as the working fluid. Inlet velocities of 0.01 m/s, 0.03 m/s, 0.05 m/s, and 0.1 m/s were applied to evaluate their influence on velocity distribution, streamline patterns, and pressure drop. A grid independence study was conducted using three mesh densities, and the final mesh with an element size of 0.015 m showed less than 1% variation in pressure drop, confirming mesh-independent results. The simulation results indicate that increasing inlet velocity significantly increases pressure drop and maximum velocity within the reaktor due to flow acceleration near the inlet region. Streamline analysis reveals the formation of recirculation zones in the lower section of panel.